Criminal Liability Of Misuse Personal Identity Number For Cellphone Cards Registration Illegally - Aziz, Ubait Kurniawan; Azizah Hidayat, Nur (Faculty of Law, Mulawarman University, 2022)
Telecommunication network is a necessity needed today and ever after. This momentum is exploited by several cheaters who looking for big profits. The one of bad trick is misuse someone else's ID card to register cellphone SIM Card so it can be sells faster. And that’s actually against not only Law no. 24 of 2013 concerning Population Administration but also Law No. 19 of 2016 concerning Amendments to Law no. 11 of 2008 concerning Information and Electronic Transactions. The regulations about criminal liability misuse ID cards other person for registration cellphone SIM card not get serious attention from government. Therefore, the purposes of this research are : (1) using someone else's Personal Identity Number and Family Identity Number for cellphone SIM Cards registration illegally is an act of crime; (2) criminal liability of misuse other people's Personal Identity Number and Family Identity Number for registration cellphone SIM Cards based on the ITE Law and the Population Administration Law. This research using normative legal research, while methods using Statute Approach and Conceptual Approach. The results of this research found criminal liability sanctions for misuse someone else’s Personal Identity Number and Family Identity Number for registration cellphone SIM Cards illegally based on the ITE Law, the Criminal Code Law, and the Population Administration Law.